Changes in the Understanding of Work in Religious Zionist Thought: Rabbi T.I. Thau as a Case Study - Mashiaḥ, Amir (Religions, 2018)
In Jewish religious texts, Torah study is placed at the top of the hierarchy of values. This suggests that work as such is of no religious significance; work is rather a prerequisite for the real essentials of life. The Mizrachi religious Zionist movement, founded in 1902 by R. Yitzhak Yaakov Reines (1839-1915), introduced a markedly different view. The movement upheld a concept of work as a religious value, not only an existential need. Later religious Zionist thinkers developed a dialectical notion of the mutual integration of the Torah and labor; this eventually became the motto of the Bnei Akiva youth movement that they inspired. With time, the theological approach of R. Kook the Elder (ReAYaH) and of R. Kook the Younger (RTziYaH) became dominant in religious Zionism. R. Kook the Elder founded the yeshivah at Merkaz ha-rav in Jerusalem, which he also headed; his son eventually succeeded him. To date, the yeshivah has produced a great number of students and rabbis, who made the teaching of the two Rabbis Kook the legacy of the religious Zionist community as a whole. The aim of the present article is to trace the changes taking place in the religious Zionist attitude toward work as this is articulated in the thought of a student of the two Rabbis, Kook whom many regard as the continuator of their teaching today. This is Rabbi Tzvi Israel Thau (b. 1937), one of the most influential rabbinic figures associated with religious Zionism, President of Yeshivat har ha-mor and the spiritual leader of the Torah academies referred to as yeshivot of the line [ha-kav].